2017
DOI: 10.4103/0366-6999.209896
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy in Keloids Treatment

Abstract: Objective:Radiation therapy combined with surgical excision was considered as one of the most effective treatment plans for keloid lesions. However, there was no unanimity found over present literatures regarding the issue on optimized treatment strategy for keloids. We here provide a comprehensive review over this issue and emphasize on the influencing factors.Data Sources:The data analyzed in this review were searched from articles included in PubMed and EMBASE databases.Study Selection:The original articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 70 publications
1
29
1
1
Order By: Relevance
“… 77 Radioactive skin patches have also been used in combination with other treatment modalities for keloids. 78 , 79 Radiotherapy is most commonly used 24–48 h after surgical excision 74 , 80 and acts by suppressing angiogenesis and inhibiting fibroblast activity. 1 Decreased fibroblast proliferation, induced cell senescence and apoptosis, leading to reduction in collagen production and suppression of keloid development have also been reported.…”
Section: Current Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“… 77 Radioactive skin patches have also been used in combination with other treatment modalities for keloids. 78 , 79 Radiotherapy is most commonly used 24–48 h after surgical excision 74 , 80 and acts by suppressing angiogenesis and inhibiting fibroblast activity. 1 Decreased fibroblast proliferation, induced cell senescence and apoptosis, leading to reduction in collagen production and suppression of keloid development have also been reported.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…19 A recommended radiation dose > 30 Gy over several sessions can also minimise adverse effects. 19 , 80 Radiotherapy carries a risk of malignancy. 85 , 86 Therefore, caution should be used in radiation-vulnerable sites such as the head, neck, thyroid and breast, and in patients aged < 18 years.…”
Section: Current Treatmentsmentioning
confidence: 99%
“…For large and refractory keloids, surgical resection combined with radiotherapy is a very effective and reliable method of treatment. 15 18 Shen et al. 19 retrospectively analyzed 834 cases of keloid lesions in 568 patients and reported that large-segment electron-beam radiation (18 Gy/2 fr, 1 week apart) postoperatively (within 48 hours) can reduce the recurrence rate of keloids to 11.75%.…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects are hyperpigmentation and hypopigmentation [ 4 ]. The theoretical risk of malignancy as a side effect from radiation therapy has been discussed ever since the implementation of this treatment, however, a 2019 comprehensive review of radiation therapy for keloids suggests that this risk remains negligible [ 8 ]. The current consensus regarding radiation therapy for keloids is that it is safe and effective for treating keloid scars with minimal long-term risk.…”
Section: Reviewmentioning
confidence: 99%